Evaluation of the Local Content Learning Program for Local Language in Jayapura District Using the CIPP Evaluation Model - Koirewoa, Fred Samuel; Dwikurnaningsih, Yari (International Journal of Social Service and Research, 2023)
Local governments in Indonesia through schools are starting to be moved to teach local languages as local content lessons to protect local local languages. Jayapura district also implements local content of the local language. This study aims to evaluate the Local Language Learning Program in Jayapura District. This research was evaluative research with CIPP model and using a qualitative approach. The data analysis technique used was Miles and Huberman. The formulation of the problem in this study was that the Regional Language Local Content Learning program in Jayapura Regency has been running since 2022 and, in fact, faces various obstacles; for this reason, it is necessary to conduct a thorough evaluation research on this program. Data collection techniques in this study were carried out by means of interviews, documentation studies, and observations. The results obtained in this study include in the context dimension, it is found that the local language local content program in Jayapura Regency was implemented quite well. In the input dimension, this program is also in the sufficient category. The process dimension in this study is also in the sufficient category. Then the product evaluation, has less results.